Studi Komputasional Senyawa Flavonoid Tanaman Obat sebagai Kandidat Agen Antidiabetik - Amin, Saeful; Hurry, Zulfan Alfairuz Zabbady; Sumantri, Tri Adi; Fauzi, Rifqi Ahmad (Penerbit Goodwood, 2024)
Purpose: This study aimed to investigate the potential of natural flavonoid compounds brazilin, luteolin, and butein as antidiabetic agents by exploring their interactions with key molecular targets in type 2 diabetes mellitus. Methodology/approach: This research was conducted using a computational approach involving molecular docking and pharmacokinetic prediction. Docking simulations were performed using AutoDock Vina and PyRx to evaluate the binding affinity of the selected flavonoids to the enzymes ?-glucosidase, ?-amylase, and glucokinase. Results/findings: The results showed that All three flavonoids exhibited strong binding affinities to ?-glucosidase and ?-amylase, indicating their potential to inhibit carbohydrate-digesting enzymes. Conclutions: Flavonoids from medicinal plants have potential as natural antidiabetic agents by inhibiting glucose-metabolizing enzymes and modulating insulin pathways. Computational studies have shown strong target interactions and favorable pharmacokinetic profiles, although further in vitro and in vivo validation is needed. Limitations: The findings of this study were limited to in silico data, and further validation through in vitro and in vivo experiments is necessary to confirm their effectiveness and safety. Contribution: This research contributes to the field of pharmaceutical sciences and natural product-based drug development, providing valuable insights for researchers and healthcare professionals interested in alternative therapies for diabetes management.